Kommentare zur Taxonomie der Symphyta (Hymenoptera). (Vorarbeiten zu einem Katalog der Pflanzenwespen, Teil 1). - Taeger, Andreas; Blank, Stephan M. (Contributions to Entomology = Beiträge zur Entomologie, 1996)
In the course of preliminary studies for a catalogue of sawflies (Hymenoptera: Symphyta) nomenclatural problems are clarified. The type species of the genera Dolerus Panzer, 1801, Mesoneura Hartig, 1837, and Nematinus Rohwer, 1911 are designated and Dolerus (Equidolerus) subgen. nov. is described (= Dosytheus auct.). The following new synonyms of generic names are indicated: Croesus Curtis, 1824, syn. nov. (= Craesus Leach, 1817); Dosytheus Leach, 1817, syn. nov. (= Dolerus Panzer, 1801); Phaenusa Cameron, 1875, syn. nov. and Phoenusa Ed. André, 1880, syn. nov. (= Fenusa Leach, 1817); Pristis Brullé, 1846, syn. nov. (= Mesoneura Hartig, 1837); Anatoliroa Muche, 1983, syn. nov. (= Seljukia Benson, 1966). Messa Leach, 1817 cannot be interpreted. Fenusella Enslin, 1912 has to be used for Messa auct. Within the species-group 24 nominal taxa are synonymized and 24 new combinations are proposed (cf. index). The following replacement names are proposed: Tenthredo fredericki nom. nov. pro T. fallax F. Smith, 1878; T. compressicornuta nom. nov. pro T. compressicornis Cameron, 1899; T. clavicornuta nom. nov. pro T. clavicornis Konow, 1898; T. kuznetzovi nom. nov. pro Tenthredella eximia Kuznetzov-Ugamskij, 1927.The Symphyta described by F. Klug are listed with their correct original citations. Species lists for Aglaostigma W. F. Kirby, 1882, Craesus Leach, 1817, and Fenusella Enslin, 1912 are presented.KeywordsTenthredinidae, designation of type species, replacement names, new combinations, new synonyms, new subgenus, dates of publications.Nomenclatural Actsalpinum (Thomson, 1871) (Aglaostigma), comb. n. hitherto Perineura alpinasinicum (Takeuchi, 1940) (Aglaostigma), comb. n. hitherto Laurentia sinicaanatolica Muche, 1983 (Anatoliroa), syn. n. of Seljukia tenebrosa Benson, 1966singularis (Malaise, 1931) (Conaspidia), comb. n. hitherto Eriocampa singularisEquidolerus Taeger & Blank, 1996 (Dolerus), sgen. n.konowi Lacourt, 1989 (Elinora), syn. n. of Elinora maculipes (Lepeletier, 1823)maculipes (Lepeletier, 1823) (Elinora), comb. n. hitherto Tenthredo maculipespallidipes (Dalla Torre, 1894) (Elinora), comb. n. hitherto Allantus pallidipesplana (Jakovlel, 1892) (Empria), comb. n. hitherto Poecilosoma planaalaskana (Kincaid, 1900) (Fenusella), comb. n. hitherto Fenusa alaskanaglaucopsis (Konow, 1907) (Fenusella), comb. n. hitherto Fenusa glaucopsishortulana (Klug, 1818) (Fenusella), comb. n. hitherto Tenthredo (Emphytes) hortulanajavana (Enslin, 1912) (Fenusella), comb. n. hitherto Messa javanaleucostoma (Rohwer, 1910) (Fenusella), comb. n. hitherto Parabates leucostomanana (Klug, 1816) (Fenusella), comb. n. hitherto Tenthredo (Allantus) nanapopulifoliella (Townsend, 1893) (Fenusella), comb. n. hitherto Blennocampa populifoliellaseptentrionalis (Koch, 1990) (Fenusella), comb. n. hitherto Messa septentrionalistaianensis (Xiao & Zhou, 1983) (Fenusella), comb. n. hitherto Messa taianensisxylostei (Vallot, 1836) (Hoplocampoides), comb. n. hitherto Tenthredo xylosteimatsumurai (Vikberg, 1982) (Nematinus), comb. n. hitherto Nematus matsumuraiacuminatus Vikberg, 1982 (Nematus), syn. n. of Nematus acuminatus (Lindquist, 1968)brunnescens Vikberg, 1983 (Nematus), syn. n. of Nematus brunneus (Lindquist, 1971)glaber Vikberg, 1982 (Nematus), syn. n. of Nematus politus (Lindquist, 1974)squamicauda Vikberg, 1982 (Nematus), syn. n. of Nematus caudalis (Lindquist, 1968)truncicollis Vikberg, 1982 (Nematus), syn. n. of Nematus curticornis (Lindquist, 1969)berolinensis Muche, 1971 (Pachynematus), syn. n. of Amauronematus humeralis (Lepeletier, 1823)xylostei Giraud, 1863 (Selandria), syn. n. of Hoplocampoides xylostei (Vallot, 1836)excellens Kuznetzov-Ugamskij, 1927 (Tenthredella), syn. n. of Tenthredo tumida (Mocary, 1909)Anatoliroa Muche, 1983 (Tenthredinidae), syn. n. of Seljukia Benson, 1966Craesus Leach, 1817 (Tenthredinidae), stat. rev. the name "Croesus Curtis, 1824" is an unjustified emandationCroesus Curtis, 1824 (Tenthredinidae), syn. n. of Craesus Leach, 1817 (unjustified emandation)Dosytheus Leach, 1817 (Tenthredinidae), syn. n. of Dolerus (Dolerus) Panzer, 1801Fenusella Enslin, 1912 (Tenthredinidae), gen. rev. not a synonym of Messa Leach, 1817Phaenusa Cameron, 1875 (Tenthredinidae), syn. n. of Fenusa Leach, 1817 (unjustified emendation)Phoenusa Ed. André, 1880 (Tenthredinidae), syn. n. of Fenusa Leach, 1817 (unjustified emendation)Selandria (Pristis) Brullé, 1846 (Tenthredinidae), syn. n. of Mesoneura Hartig, 1837amplicapitata Zombori, 1974 (Tenthredo), syn. n. of Tenthredo (Tenthredella) stigma (Forsius, 1918)cameroni Malaise, 1945 (Tenthredo), syn. n. of Tenthredo (Olivacedo) ebba Benson, 1914kerketa Dovnar-Zapolskij, 1930 (Tenthredo), syn. n. of Tenthredo (Tenthredo) albiventris albiventris (Mocsáry, 1880)pappi Zombori, 1978 (Tenthredo), syn. n. of Tednthredo (Olivacedo) eduardi Enslin, 1920sortitor Malaise, 1938 (Tenthredo), syn. n. of Tenthredo (Tenthredella) abdominalis (Matsumura, 1912)stubbei Koch, 1984 (Tenthredo), syn. n. of Tenthredo (Tenthredella) borea Enslin, 1920vinimalis Fallén, 1808 (Tenthredo), syn. n. of Trichiocampus grandis (Lepeletier, 1823); praeocc. by vinimalis Schrank, 1796vivida Malaise, 1931 (Tenthredo), syn. n. of Tednthredo (Olivacedo) eduardi Enslin, 1920fredericki Taeger & Blank, 1996 (Tenthredo (Olivacedo)), nom. n. pro Tenthredo fallax F. Smith, 1878, nec Lepeletier, 1823hybrida Erichson, 1851 (Tenthredo (Poecilostoma)), nom. praeocc.; syn. n. of Tenthredo hybrida Evdersmann, 1847; now a synonym of Empria plana (Jakovlev, 1892)abdominalis (Matsumura, 1912) (Tenthredo (Tenthredella)), comb. n. hitherto Tenthredopsis abdominaliscompressicornuta Taeger & Blank, 1996 (Tenthredo (Tenthredella)), nom. n. pro Tenthredo compressicornis Cameron, 1899, nec Fabricius, 1804brunnea (Cameron, 1899) (Tenthredo (Tenthredina)), comb. n. hitherto Allantus brunneusclavicornuta Taeger & Blank, 1996 (Tenthredo (Tenthredo)), nom. n. pro Tenthredo clavicornis Konow, 1898, nec Fabricius, 1781kuznetzovi Taeger & Blank, 1998 (Tenthredo (Tenthredo)), nom. n. pro Tenthredella eximia Kuznetzov-Ugamskij, nec Norton, 1868nivosa (Klug, 1817) (Tenthredopsis), comb. n. hitherto Tenthredo (Allantus) nivosagrandis (Lepeletier, 1823) (Trichiocampus), comb. n. hitherto Nematus grandis